Spectroscopic studies of new Co(II), Cu(II), and Ni(II) complexes with 1,2-bis(m-aminophenoxy)ethane - Temel, Hamdi; Soran, Serap; Sekerci, Memet (Maik Nauka/Interperiodica/Springer, 2007)
1,2-Bis(m-aminophenoxy) ethane was prepared in a one-stage process. In this reaction, Pd/C was used as a catalyst. 1,2-Bis( m-aminophenoxy) ethane was synthesized from 1,2-bis(m-nitrophenoxy) ethane. Diamine complexes [CoLCl2], [CuLCl2] and [NiL2] Cl-2 have been synthesized and characterized by elemental analyses, Lambda(M), IR, UV-Vis, H-1 NMR and magnetic measurements.
Keywords: Schiff-Base; Cobalt(Ii); Copper(Ii); Zn(Ii)